The ionic and protonation states of flavin control the activation and recovery of Drosophila cryptochrome - Wenlong Xie; Mengqi Wan; Yuting Dai; Yingjun Jiang; Mohan Wang; Lili Zhou; Li Zhang; Linmei Sun; Xiaoyu Feng; Tian Xia; Bin Wen; Jun Lv; et al. (Communications Chemistry)
Abstract Drosophila cryptochrome (dCry) is a flavin-containing photoreceptor. The release of C-terminal tail (CTT) upon illumination is a crucial step for the light sensing of dCry. Here, we demonstrated that both anionic semiquinone (asq) and anionic hydroquinone (hq) triggered CTT release, while neutral semiquinone (nsq) formation suppressed it. However, during photoreduction, a fraction of nsq was formed in dCry under neutral conditions, and the fraction of which increased when the pH decreased. The proton required for nsq formation might be transferred to flavin through a side tunnel. The nsq formation was minimized in dCry under basic conditions, or in the mutants in CTT, which resulted in enhanced CTT release but slower oxidation (i.e. recovery) after photoreduction. Therefore, forming a proper fraction of nsq is important for fast recovery of dCry after light sensing. Nevertheless, a key residue at the side tunnel, His378, is a proton interceptor that adjusts the nsq formation.